Process Management Maturity Versus Management Processes Maturity: A Machine Learning Approach - Lucia – Cristina FARKAS; Alexandru - Costin BAROIU (Communications of International Proceedings, 2021)
Today’s businesses compete in faster, better and smarter markets. They are required to find the best solution at the lowest cost in order to succeed. Therefore, they need to implement optimization techniques, such as business process management (BPM) models. A specific type of processes found in organizations are management related ones. The purpose of this article is to present that, even if the two concepts seem familiar, process management and management processes, they are oftentimes applied to different areas, both in research and in business. The article analyzes the dynamics between the two from the perspective of maturity, more specifically maturity models developed for process management and for management processes. The article proposes a Machine Learning technique, Clustering, in order to partition a corpus of over 2,500 articles related to the two concepts previously introduced. This technique enables researchers to quickly extract information from a large dataset of articles. The discussion is made that there are differences, management processes maturity being a more focused topic, found mostly in relation with project management, while process management maturity is found connected to a plethora of fields.
Keywords: Process management; Management process; Maturity model; Maturity of Process management; Maturity of man-agement processes; Machine Learning; Clustering